The Sustainable Development Goals Report 2017 - United Nations Department of Economic; Social Affairs (United Nations, 2017)
The aim of this report is to present an overview of the 17 Goals using data currently available to highlight the most significant gaps and challenges. The latest data show that one eighth of humankind still lives in extreme poverty and that 800 million people suffer from hunger, and that water scarcity affects more than a quarter of humanity. These statistics show how important coordinated global data-generation efforts are in supplying reliable and timely data for systematic follow-up and progress reviews.